Nocturnal Oxygenation and Periodic Breathing Profiles over time in Healthy Acute High Altitude Sojourners - Ju, Jia-Der (2019)
Study Objectives Assess acute changes in nocturnal sleep oxygenation, sleep disordered breathing and symptoms of Acute Mountain Sickness (AMS) in healthy High Altitude (HA) sojourners. Methods Ten subjects born at Sea Level (SL) were enrolled and underwent nocturnal polygraphy for 5 consecutive nights at HA and 2 nights before and after HA (2761 m). Nocturnal oxygen profiles were characterized by the mean Oxyhaemoglobin Saturation (SpO2) during sleep, and sleep apnea severity was represented by the Apnea-Hypopnea Index (AHI). Repeated measures linear regression was used to examine responses in outcome variables (SpO2, logAHI and LLS) between HA and SL. Mean SpO2 on night 1 at HA was used to stratify post-hoc analyses based on mean level of nocturnal desaturation and logAHI. Subjects completed the Lake-Louise Score (LLS) survey every day. Results Compared to SL, mean SpO2 was lower at HA (p<0.0001) and logAHI was higher at HA (p<0.0001). SpO2 increased progressively (p<0.001) while logAHI remained high at HA (p<0.978). Those with marked decreases in SpO2 at HA initially exhibited progressive increases in SpO2 over the week sojourn to levels observed in the mild desaturators. Compared to subgroups with low AHI those with high AHI showed a trend towards higher LLS (∆LLS, 0.7±0.3, p=0.16). Conclusion Nocturnal SpO2 decreased acutely at HA and increased over time, whereas sleep apnea increased and remained elevated over a one-week sojourn. The latter tends to predict elevations in LLS, while mean nocturnal SpO2 deteriorated acutely but improved over time. Nocturnal sleep disordered breathing at HA could predict acute mountain sickness and compromise daytime function.